EFEKTIVITAS DAN KONTRIBUSI PAJAK HOTEL TERHADAP PENDAPATAN ASLI DAERAH (Studi di Pemerintah Daerah Kota Semarang) - Irwan Syah; Abdul Rohman (Diponegoro Journal of Accounting, 2014)
The purposes of this research are: (1) to know the growth of tax revenue in the Semarang City hotel through 2009-2013(2) to know the effectiveness of Semarang city hotel tax revenue based on its classification through 2009-2013, (3) to identify the contribution of hotel tax against Semarang regional income through 2009-2013.This research used quantitative-descriptive method. The techniques of data collection are documentation and interview. The data which used in this research are the potential of hotel tax, the realization of hotel tax report, and the realization of original regional income. The data were analyzed using time series analysis, the effectiveness analysis and the contribution analysis.Based on the results of this research, the conclusions are: (1) the growth of hotel tax had fluctuation, the highest development of hotel tax in 2011 is 35,293 % and the lowest development in 2009 is 3,661 %(2) the revenue of hotel tax in Semarang city based on its classification from 2009 until 2013 isn’t effective. 2) The revenue of hotel tax does not have contribution against original regional income of Semarang city during 2009 until 2013.